Serous cystadenoma of pancreas: A clinicopathologic experience of 23 cases from a major tertiary care center. (November 2018) - Tariq, Muhammad Usman; Ahmad, Zubair; Abdul-Ghafar, Jamshid; Din, Nasir Ud
Background: Serous cystadenomas of pancreas are rare benign epithelial neoplasms, which predominantly occur in the pancreatic body and tail of elderly females. Majority of these tumors have microcystic appearance. Macrocystic and solid variants have also been described. A number of more aggressive cystic pancreatic lesions are included in the differential diagnosis. Distinction from such lesions is important for optimal management. Objective: Our aim was to study the clinical and histological features of serous cystadenomas which would be helpful in making their correct diagnosis and understanding their behavior. Methods: We reviewed 23 cases of serous cystadenomas diagnosed in our institution between January 2001 and June 2018. Results: Mean age at presentation was 53.43 years. Female to male ratio was 4.75:1. Over half (56.5%) of the cases were diagnosed incidentally. Abdominal pain was the most common symptom. Body and tail (either alone or in combination) were the most common locations. Tumor size ranged from 2 to 16 cm. Central scar was seen in 43.4% cases. Two cases were unilocular (macrocystic). Microscopically, all cases showed simple cuboidal to flattened epithelium with round, uniform nuclei, and glycogen-rich clear cytoplasm. Focal micropapillae formation was seen in eight cases (34.7%). Surgical resection was performed in 82.6% cases. Recurrence occurred in only one single case. Conclusion: Pancreatic serous cystadenomas are benign neoplasms with excellent prognosis. The tumors showed typical morphological features in all cases. Surgical resection was performed in the majority of cases in our study owing to lack of optimal and complete radiological workup pre-operatively and the concern for not missing and adequately treating pancreatic mucinous cystic neoplasms.